Makna Kehidupan Beragama Bagi Generasi Zaman Ini - Najwa Adillah Masnur; Azzahra Hafiza; Jihan Nailah Putri; Rizki tiandri; Wismanto Wismanto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Religion is not only a belief but also a means to make people feel the presence of God. The view of religion should be lived and practiced in daily life. In modern life, there are many ways people view religion. Others see it as something that must be practiced in daily life, while others see religious beliefs as something that must be practiced as part of the rituals of worship. Modern life presents challenges to those caught up in media technology, the crisis of meaning causes religion to no longer be considered a necessity and only a formality. Everyone has a different way of determining their life goals in the face of all forms of erosion of faith, so that there are various ways to interpret religion. There are various ways to interpret religion.